Autologous Breast Reconstruction after Failed Implant-Based Reconstruction: Evaluation of Surgical and Patient-Reported Outcomes and Quality of Life. Issue 2 (February 2019) - Coriddi, Michelle; Shenaq, Deana; Kenworthy, Elizabeth; Mbabuike, Jacques; Nelson, Jonas; Pusic, Andrea; Mehrara, Babak; Disa, Joseph J.
Abstract : Background: There is a subset of patients who initially undergo implant-based breast reconstruction but later change to autologous reconstruction after failure of the implant reconstruction. The purpose of this study was to examine outcomes and quality of life in this group of patients. Methods: After institutional review board approval, a retrospective chart review of a prospectively maintained database was performed and BREAST-Q surveys were evaluated. Results: One hundred thirty-seven patients underwent autologous breast reconstruction following failed implant-based reconstruction with 192 total flaps. Failure of implant reconstruction was defined as follows: capsular contracture causing pain and/or cosmetic deformity [ n = 106 (77 percent)], dissatisfaction with the aesthetic result [ n = 15 (11 percent)], impending exposure of the implant/infection [ n = 8 (6 percent)], and unknown [ n = 8 (6 percent)]. Complications requiring operative intervention included partial flap loss [ n = 5 (3 percent)], hematoma [ n = 5 (3 percent)], vascular compromise requiring intervention for salvage [ n = 2 (1 percent)], and total flap loss [ n = 1 (1 percent)]. Thirty-four patients (23 percent) had BREAST-Q surveys. There was a statistically significant increase in overall outcomes ( p < 0.001), satisfaction with appearance of breasts ( p < 0.001), psychosocial well-being ( p < 0.001), and physical well-being of the chest ( p = 0.003). A statistically significant decrease in physical well-being of the abdomen was observed ( p = 0.001). Conclusions: Autologous breast reconstruction after failed implant-based reconstruction has an acceptable complication rate and is associated with significantly improved patient satisfaction and quality of life. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Evidence-Based Outcomes Article.